Comunicación asertiva y el rendimiento académico en estudiantes del cuarto grado de primaria de la I.E.P.P.S Rosa Agustina Donayre de Morey, Iquitos 2024 - Acosta Valera, Darly Jecenia (2025)
The general objective of the study was: "To determine the relationship between assertive communication and academic performance in fourth grade students of primary school at the educational institution N° 0557413 "Rosa Agustina Donayre de Morey”,, Iquitos 2023, The sample consisted of 127 fourth grade students of said educational institution. The data obtained were analyzed in an exploratory manner, based on descriptive statistical procedures, with measures of central tendency and dispersion. The use of figures allowed the representation of multiple responses referring to each variable. The results show that within the educational field, assertive communication affects performance and school performance, where it can be mentioned that there are deficiencies in the aspect of communication between students, teachers and administrative staff. Therefore, it is essential to consider future strategies that allow improving the performance of this communicative skill. The work concludes that there is a relationship between assertive communication and academic performance among fourth grade students. It is recommended to implement spaces for coexistence, where it is possible to strengthen the communication of all members of the educational community, as well as, on their own initiative, create and involve dynamic activities that promote participation and interaction in relation to what is planned, where, it is possible to see a better performance in students in relation to the directed activities, which is reflected in their academic performance.